Proton affinity Revisited: Benchmarking computational approaches for accurate predictions - Mathew, Manjesh; Puchta, Ralph; Thomas, Renjith (Computational and Theoretical Chemistry, 2024)
Proton affinities and gas phase basicities, starting from small molecules like ammonia up to proton sponge like PMG (N,N,N|,N|,N|-Pentamethylguanidine) were calculated with cost-effective, but accurate computational methods B3LYP, BP86, PBEPBE, APFD, wB97XD, and M062X using the flexible def2tzvp basis set and compared with experimental results. Different error methods were used to study the variations from experimental results. Most of these methods gave good results, but M062X was slightly better with minimum error in all examples containing hetero atoms. The APFD and wB97XD functionals tend to overestimate values and do not perform as well. The effectiveness of Grimme's dispersion corrections on the basicity was also tested, but found to be ineffective. The accuracy of different functionals in predicting the N[sbnd]N bond length in DAN (1,8-Diaminonaphthalene) and DMAN(1,8-bis(dimethylamino) naphthalene was tested. APFD, wB97XD and M062X agree well with reported values.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Benchmarking Study; Computational Chemistry; Gas Phase Basicity; Organic Compounds; Proton Affinity; Quantum Chemical Methods